USE OF INHALED CORTICOSTEROIDS IN PEDIATRIC ASTHMA: THE ROLE OF PHARMACEUTICAL CARE IN TREATMENT ADHERENCE AND SAFETY (REMUNOM, 2025)
Asthma is a common chronic disease in childhood, characterized by persistent airway inflammation and recurrent episodes of dyspnea, wheezing, and coughing. Maintenance treatment with inhaled corticosteroids (ICS) is considered the first choice for controlling persistent asthma in children, due to its effectiveness in reducing exacerbations and improving lung function. However, adherence to treatment remains a challenge, especially during asymptomatic periods. Objective: This study aims to evaluate the safety and adherence to the use of ICS in the pediatric population, highlighting the pharmacist's role in clinical care. Method: This is an integrative literature review, based on published studies obtained from databases such as PubMed and SciELO. Data analysis showed that pharmaceutical interventions, including health education, correction of inhalation technique, and continuous monitoring, contribute to greater adherence to treatment and safety in the use of medications. Expected Results: The results point to the fundamental role of the pharmacist in promoting the rational use of ICS and improving the quality of life of asthmatic children.